Pemikiran Pendidikan Islam dalam Perspektif Az-Zarnuji - Annisa Caniago; Sri Wahyuni Lubis; Azizah Hanum OK (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
Focusing on its comprehensive approach to character formation and individual growth, through analysis of the educational thought of Az-Zarnuji, a famous Islamic thinker from the 12th century. The purpose of this article is to examine Az-Zarnuji's writings about education in order to understand his beliefs in educational ideals, pedagogical approaches, and the importance of character education. This study analyzes Az-Zarnuji's main points by utilizing a text analysis and literature review approach. Based on his findings, Az-Zarnuji concluded that educating people to be happy and successful both in this world and the afterlife is the main goal of education. An emphasis on active learning, conversation, and reflection characterizes his pedagogical approach, which integrates theoretical understanding with real-world experience. Az-Zarnuji continued, character education is very important to create ethical and responsible humans. This article examines an educational initiative spearheaded by Az-Zarnuji to spread core ethical principles, including compassion, humility, perseverance, and honesty. The ideas put forward by Az-Zarnuji are very relevant considering modern educational practices. In this essay, we see how Az-Zarnuji's educational philosophy can influence the creation of a character-based curriculum and how teachers can provide the best service to their students by being an inspiration and role model. Teachers can do their part to instill strong moral character and commendable traits in the next generation by familiarizing themselves with Az-Zarnuji's educational philosophy and practicing its teachings.